POSITION OF LOCAL GOVERNMENTS TOWARD VOTER PARTICIPATION IN THE ELECTION OF LOCAL HEADS ACCORDING TO LAW NUMBER 10 OF 2016 CONCERNING THE ELECTION OF GOVERNOR, REGENCY AND MAYOR - Fathullah Fathullah (AMAL INSANI (Indonesian Multidiscipline of Social Journal), 2022)
Regional Government, one part of state institutions, has the function of regulating and implementing laws, one of which is realizing democracy (election of regional heads). Democracy is one of the main pillars regarding human beings; as individuals, society, nation, state and society. Do government and democracy contradict each other or complement each other in their respective functions. Democratic government is a government that emphasizes the values ​​of justice and community participation. Community participation in democracy is a right based on the law. What is the responsibility of the Regional Government in democracy according to the 1945 Constitution of the Republic of Indonesia, and Law Number 10 of 2016 concerning the Election of Governors, Regents, and Mayors, with regard to public participation. The results of the study show that the functions and roles of local governments in democracy are complementary and complementary. The law regulates the government's responsibility to increase public participation, namely voters. Government and democracy emerged at the will of the people from the gift of God Almighty as a resistance to the notion of authoritarian power, to provide guarantees for the rights of individuals, communities, nations, and states. Democracy and participation are inseparable from the state constitution and laws and regulations. The implementation of democracy by the Regional Government must be carried out in accordance with the laws and regulations and the values ​​that live in society, the State Philosophy, Pancasila and the 1945 Constitution.   Keywords: Local Government, Regional Head Election, Voter Participation, Law